1995
DOI: 10.1557/proc-390-245
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Secondary Ion Mass Spectrometry to Investigate Wire Bonding Yield Problems on Gold Contacts

Abstract: With ongoing demand for high density wiring and high I/O on VLSI chips, the requirement of high wire bond yield is a challenge to achieve low cost, high performance and reliable products. Secondary Ion Mass Spectrometry (SIMS) was used to investigate the metallurgical contaminants on the gold wire bond pads and their impact on wire bond yields. SIMS depth profile studies showed that copper and nickel in concentrations greater than 1 wt% caused poor wire bondability, while copper concentration at less than 0.1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Most work has concentrated on bond pad contamination where it has been shown that it results in reduced bond strength and bondability. [1] Surface characterization of the bond pads is relatively straightforward due to their simple geometry. Less studied is contamination on the wire itself.…”
Section: Introductionmentioning
confidence: 99%
“…Most work has concentrated on bond pad contamination where it has been shown that it results in reduced bond strength and bondability. [1] Surface characterization of the bond pads is relatively straightforward due to their simple geometry. Less studied is contamination on the wire itself.…”
Section: Introductionmentioning
confidence: 99%